Half a minute - Basia, Basia Trzetrzelewska; White, Danny; Sony Music Entertainment (New York : Sony Music Entertainment, 1995)
Contains two tracks taken from the Epic Release: Basia on Broadway recorded at the Neil Simon Theatre, Broadway, NY on 24th and 25th November 1994.
CD 1 : Half a minute (Remix) / (3:50) -- Live / (3:57).
Koleksi Khas Wiramanja.
Title from disc label.